ORIENTALISM AND CULTURAL HEGEMONY IN SEXY BY JHUMPA LAHIRI: A POSTCOLONIALISM APPROACH - Rahmadina Vita Jannah; Dyah Uyun Wulandari; Qirara; Ima Dyah Savitri; Jiphie Gilia Indriyani; Shabrina An Adzhani (2025)
This paper examines the themes of orientalism and cultural hegemony in Jhumpa Lahiri’s short story Sexy through the lens of postcolonial theory, particularly Edward Said’s concept of Orientalism and Gramsci’s hegemony. The narrative explores the dynamics between Miranda, a white American woman, and Dev, a married Indian man, highlighting the fetishization of Eastern culture and the alienation faced by diasporic individuals. Lahiri portrays how the West's portrayal of the East as exotic and